Kinetics and kinematics of the block phase of elite para swimming starts - Van Caekenberghe, I.; Payton, C. (ISBS Proceedings Archive (Michigan), 2017)
The present study presents a preliminary overview of dive start performance variables of the block and entry phase of elite para swimmers measured using the Kistler Performance Analysis Swimming System. Insight is given into the variability of these measures. These results can be used as a reference when examining the start phase in training.